2009
DOI: 10.3109/02841850903220371
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of multislice computed tomography and magnetic resonance imaging in the diagnosis of retroperitoneal spread of testicular cancer: a literature review

Abstract: Testicular cancer is the most frequent malignant disorder in men aged 15-35 years. Generally, diagnosing and follow-up include computer tomography (CT) examinations to detect possible retroperitoneal spread (abdomen and pelvis), resulting in at least eight CT examinations. This patient group is thereby exposed to a non-neglectable radiation dose, increasing the risk of future radiation-induced secondary cancer. This is especially problematic in potentially surgically cured patients with stage 1 testicular canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…The majority of panelists voted against performing biopsies in EGCC patients when both of the testes were normal upon clinical examination and ultrasound (supplementary material S3, available at Annals of Oncology online). Spiral computerized tomography (CT) scans of the thorax, abdomen and pelvis remain the staging investigation of choice (Table 1) [12]. Diagnostic imaging of the brain is recommended in patients with visceral metastases and mandatory in the presence neurological symptoms (supplementary material S4, available at Annals of Oncology online).…”
Section: Diagnosis Management Of the Primary Tumor And Stagingmentioning
confidence: 99%
“…The majority of panelists voted against performing biopsies in EGCC patients when both of the testes were normal upon clinical examination and ultrasound (supplementary material S3, available at Annals of Oncology online). Spiral computerized tomography (CT) scans of the thorax, abdomen and pelvis remain the staging investigation of choice (Table 1) [12]. Diagnostic imaging of the brain is recommended in patients with visceral metastases and mandatory in the presence neurological symptoms (supplementary material S4, available at Annals of Oncology online).…”
Section: Diagnosis Management Of the Primary Tumor And Stagingmentioning
confidence: 99%
“…Aparicio et al pointed out increased preoperative Beta-HCG level adversely affected outcome in patients with CS1 seminoma [3], as well as the findings of Vesprini D et al demonstrated HCG was the most common increased marker at the time of relapse [23]. The most accepted risk factors for STGCT are tumor size and rete testis invasion as well as the ones for NSTGCT are vascular invasion and the percentage of embryonal carcinoma [11,13,24,25]. Our study also confirmed that tumor size (OR 6.1; 95% CI 1.6-22.4) and lymphovascular invasion (OR 3.4; 95%, 1.5-7.4) were IRFs in predictive Model s2 and Model n2, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…In CS1 STGCT and NSTGCT, only approximately 20% and 30% of patients will relapse in 5 years after orchiectomy, which means about 70-80% patients will face unnecessary surgery injury from RPLND or secondary radiation-induced cancer due to frequent CT monitors (at least 79 in STGCT and 89 in NSTGCT during 5-year follow-up) [4,25]. For reducing these risks, some researchers proposed adept treatment strategy and the interval CT follow-ups depending on risk factors of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Ainsi, Rustin et al n'ont pas mis en évidence d'intérêt à réaliser 5 scanners plutôt que 2, dans le suivi de patients présentant une tumeur non séminomateuse de stade I [19] ; • remplacer les scanners par des IRM. Mais il faut pour cela prouver l'équivalence d'efficacité entre les deux méthodes dans la surveillance des cancers testiculaires, ce qui n'est pas encore le cas [20].…”
Section: Discussionunclassified